Fiddler's journey to the big screen [videorecording (DVD)] - Raim, Daniel; Sragow, Michael; Goldblum, Jeff, 1952-; Jewison, Norman, 1926-; Williams, John, 1932-; Harnick, Sheldon; Turan, Kenneth; Topol, 1935-; Harris, Rosalind; Marsh, Michele; Small, Neva; Boyle, Robert (Robert F.) (Kino Lorber, 2022)
The fall of 2021 marked the 50th anniversary of Fiddler on the Roof, the film Pauline Kael (The New Yorker) called 'the most powerful movie musical ever made.' Narrated by Jeff Goldblum, it captures the humor and drama of director Norman Jewison's quest to recreate the lost world of Jewish life in Tsarist Russia and re-envision the beloved stage hit as a wide-screen epic. Oscarʼ- nominated filmmaker Daniel Raim puts us in the director's chair and Jewison's heart and mind, drawing on behind-the-scenes footage and never-before-seen stills as well as original interviews with Jewison, Topol (Tevye), composer John Williams, production designer Robert F. Boyle, film critic Kenneth Turan, lyricist Sheldon Harnick, and actresses Rosalind Harris, Michele Marsh, and Neva Small (Tevye's daughters). This inspiring film explores how the experience of making Fiddler deepened Jewison as an artist and revived his soul.